2014
DOI: 10.1155/2014/605835
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Synergy: An Academic/Clinical Partnership for Transformational Change

Abstract: Background. A programme of postgraduate study was developed in partnership between a health board and a university in New Zealand, having identified critical thinking and practice change as key determinants of good care delivery. Aim. To explore the impact after 12 months of a postgraduate programme for registered nurses on patient assessment and clinical reasoning, and the status of implementation plans for improved patient care. Design. Outcome evaluation using a survey and focus groups. Setting. On location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Therefore, careful monitoring of workload, and individualised learning support is vital. The model of delivery with formal university teaching and clinical preceptorship in practice settings is not new but its positive impact on systematic patient assessment, clinical reasoning and care decisions reinforces the value of clinical-academic partnerships in education found elsewhere (McKillop, Atherfold, & Lees, 2014). In contrast to studies that have reported new graduates' reluctance to communicate with other health professionals (Dyess & Sherman, 2009;Fink, Krugman, Casey, & Goode, 2008), participants in this study indicated that towards the end of the programme they were confident and articulate with medical and nursing colleagues regarding patient status and safety.…”
Section: Nursing Educationmentioning
confidence: 89%
“…Therefore, careful monitoring of workload, and individualised learning support is vital. The model of delivery with formal university teaching and clinical preceptorship in practice settings is not new but its positive impact on systematic patient assessment, clinical reasoning and care decisions reinforces the value of clinical-academic partnerships in education found elsewhere (McKillop, Atherfold, & Lees, 2014). In contrast to studies that have reported new graduates' reluctance to communicate with other health professionals (Dyess & Sherman, 2009;Fink, Krugman, Casey, & Goode, 2008), participants in this study indicated that towards the end of the programme they were confident and articulate with medical and nursing colleagues regarding patient status and safety.…”
Section: Nursing Educationmentioning
confidence: 89%
“…One such theory, the Threshold Concepts learning framework, aims to identify the concepts most relevant for learning in a given discipline. Currently, newer studies have attempted to identify TC in a wide variety of disciplines such as nursing (McKillop et al, 2014 ), palliative medicine (O’Callaghan et al, 2020 ), economics (Randall et al, 2018 ), or physics (Serbanescu, 2017 ), among others.…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of TC in health sciences currently constitutes a major challenge for higher education, because of the lack of a standardized, validated method for this purpose (Santisteban‐Espejo et al, 2020 ). Although TC have initially been identified by professors and staff scholars (Davies & Mangan, 2007 ; McKillop et al, 2014 ) students' perception may also play a key role in their identification, and students' perceptions are now increasingly used in the scientific community to identify TC (Clouder, 2005 ; Loertscher et al, 2014 ; Park, 2014 ). In this connection, several authors have attempted to identify TC by investigating the perceptions of medical students after conducting clinical practice in palliative care (O’Callaghan et al, 2020 ) and pediatrics (Randall et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been described several methodological strategies with the purpose to identify TC. First attempts consisted of a fluid framework based on asking scholars to identify themselves TC in their subjects [28] or the discussion between partners [29]. These scholar-based approaches present some limitations.…”
Section: Methods For Identification Of Threshold Conceptsmentioning
confidence: 99%